In Vitro Response And Cause Of Recalcitarancy In Coconut - Chandralekha K (Department of Plantation crops and Spices, College of Horticulture, 1997)
A study was undertaken in the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara, during 1995 to 1997 to find out the in vitro response and causes of recalcitrancy in coconut (Cocos nucifera L.). Young palms of 0 x T parentage were used as source of explants in the present study. Direct and indirect organogenesis and embryogenesis were tried in various explants like zygotic embryo, immature inflorescence rachillae, anther and tender leaves. Coconut tissues usually turn brown under in vitro condition due to polyphenol interference. Addition of 0.25 per cent activated charcoal reduced the phenolic exudation effectively and was found superior to the addition of ascorbic acid or polyvinyl pyrrolidone. The phenolic exudation was considerably reduced under dark condition. Y 3 medium was found to be superior for zygotic embryo culture and growth of inflorescence tissues whereas, Blaydes medium was found suitable for anther culture. Y3 medium supplemented with 2.0 mg -1 NAA and 1.0 mg -1 kinetin was found the best for zygotic embryo culture. Immature zygotic embryos produced friable, nodular callus with higher embryogenic potential. White globular structures were produced when concentration of 2,4-0 was gradually reduced but regeneration was not obtained. Immature inflorescence rachillae explants produced friable callus when high levels of 2,4-0 was supplemented. Callusing was observed from microspores when L-glutamine 500 mg 1-1,2,4-02 mg l-1, coconut water 15 per cent v/v and 9 per cent sucrose were added to the Blaydes medium. But repeat- ability of callus induction was not obtained.